2006
DOI: 10.2975/29.2006.205.213
|View full text |Cite
|
Sign up to set email alerts
|

The personal and vocational impact of training and employing people with psychiatric disabilities as providers.

Abstract: Findings suggest that a standardized program designed to provide peer training was used successfully and participants' recovery and employability were improved. Further studies are recommended to rigorously test peer providers' impact on their clients and to examine the advantages that accrue to the agency when mental health recipients are employed as peer providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 24 publications
1
54
0
Order By: Relevance
“…For example, a review by Mueser and his colleagues on recovery-oriented illness management found that such interventions can reduce symptoms and relapse while improving quality of life. Other large-scale studies have indicated that rehabilitation and recovery interventions can affect role functioning outcomes (Cook et al 2005) while numerous studies have suggested that self-esteem and self-efficacy, quality of life and other subjective and objective measures of recovery are important outcomes that can be affected by such interventions (Cook et al 2005;Shern et al 2000;Hutchinson et al 2006a;Arns and Linney 1995). The results of studies are by no means unequivocal however in dictating which of many psychosocial outcomes should be studied.…”
Section: Methodsmentioning
confidence: 96%
“…For example, a review by Mueser and his colleagues on recovery-oriented illness management found that such interventions can reduce symptoms and relapse while improving quality of life. Other large-scale studies have indicated that rehabilitation and recovery interventions can affect role functioning outcomes (Cook et al 2005) while numerous studies have suggested that self-esteem and self-efficacy, quality of life and other subjective and objective measures of recovery are important outcomes that can be affected by such interventions (Cook et al 2005;Shern et al 2000;Hutchinson et al 2006a;Arns and Linney 1995). The results of studies are by no means unequivocal however in dictating which of many psychosocial outcomes should be studied.…”
Section: Methodsmentioning
confidence: 96%
“…Job structure and career pathway The importance of employment and the shift from consumer to provider, in order for peer workers to become valued and contributing citizens, was noted by Hutchinson and colleagues. 47 More specifically, engaging in peer training and taking courses encourages peer workers to go on to successfully pursue other educational and vocational goals.…”
Section: The Existing Evidence On Peer Worker Roles In Mental Health mentioning
confidence: 99%
“…13 Participants reported feeling more empowered after completing the programme and having higher self-worth.…”
Section: Social Outcomes and Impactmentioning
confidence: 99%